Genomic insight into strategy, interaction and evolution of nitrifiers in metabolizing key labile-dissolved organic nitrogen in different environmental niches - Liu, Qian; Chen, Yuhao; Xu, Xue-Wei (Frontiers in Microbiology, 2023)
Ammonia-oxidizing archaea (AOA) and bacteria (AOB), nitrite-oxidizing bacteria (NOB) and complete ammonia oxidizers (comammox) are responsible for nitrification in nature; however, some groups have been reported to utilize labile dissolved organic nitrogen (LDON) for satisfying nitrogen demands. In order to understand the universality of their capacity of LDON metabolism, we collected 70 complete genomes of AOA, AOB, NOB and comammox from typical environments for exploring their potentials in metabolism of representative LDON (urea, polyamines, cyanate, taurine, glycine betaine and methylamine). Genomic analyses showed that urea was the most popular LDON used by nitrifiers. Each group harbored unique urea transporter genes (AOA: dur3 and utp, AOB: utp, NOB and comammox: urtABCDE and utp) accompanied with urease genes ureABC. The differentiation in the substrate-affinity of these transporters implied the divergence of urea utilization efficiency in nitrifiers, potentially driving them into different niches. The cyanate transporter (cynABD and focA/nirC) and degradation (cynS) genes were detected mostly in NOB, indicating their preference on a wide range of nitrogen substrates to satisfy high nitrogen demands. The lack of genes involved in metabolism of polyamines, taurine, glycine betaine and methylamines in most of nitrifiers suggested that they were not able to serve as a source of ammonium, only if they were degraded or oxidized extracellularly as previously reported. The phylogenetic analyses assisted with comparisons of GC% and the Codon Adaptation Index between target genes and whole genomes of nitrifiers implied that urea metabolic genes dur3 and ureC in AOA evolved independently from bacteria during the transition from Thaumarchaeota to AOA, while utp in terrestrial AOA was acquired from bacteria via lateral gene transfer. Cyanate transporter genes cynS and focA/nirC detected only in a terrestrial AOA Candidadus Nitrsosphaera gargensis Ga9.2 could be gained synchronously with Nitrospira of NOB by an ancient LGT. Our results indicated that LDON utilization was a common feature in nitrifiers, but metabolic potentials were different among nitrifiers, possibly being intensely interacted with their niches, survival strategies and evolutions.